Transmissão de preços no mercado de cana-de-açúcar entre os Estados de São Paulo e Paraná - Tomasetto, Mariza Zeni de Castro (2010)
The aim of this study was to analyze the spatial price transmission between the sugarcane markets of Sao Paulo and Paraná, from January 1995 to February 2009. The study adopted the Box-Jenkins method for models of Auto Regressive Moving Average (ARIMA) applied to time series, the unit root Augmented Dickey-Fuller test (ADF), an Engle-Granger cointegration test, a transfer function model and the Error Correction Model (MCE). The results indicated that the series are co-integrated, that is, there is long-term relationship. The elasticity of price transmission, both the long-term and the short-term, presented itself inelastic. Furthermore, it is observed, in the short-term, an unanticipated shock in the price of the sugarcane in Sao Paulo in the magnitude of 41.19% to the price of the sugarcane in Paraná. In the long term, unanticipated shocks in the price of sugarcane in São Paulo are transmitted with a magnitude equal to 99.84%. This relationship is inelastic, though very close to a unitary elasticity. Therefore, it can be concluded that even though the Law of One Price is not validated, this result shows a high degree of spatial integration of prices between the two markets, as expected.